MEDIA SOSIAL SEBAGAI SARANA PROMOSI POTENSI DESA - Mohammad Insan Romadhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Publication becomes a very important thing in introducing or promoting thepotential of an area of any kind, be it the potential of human resources and thepotential of natural resources. In the era of Internet technology that has notprogressed as it is today, the first publication into an expensive thing to do, becausein publishing an information can only through newspapers and television, but withadvances in information technology, especially the internet makes anyone can publishany information very Easy and with very low cost too, especially with the developmentof social media. Social media is defined as an online medium where its users can easilyparticipate. Participate in the sense that someone will easily share information, createcontent or content to be conveyed to others, comment on inputs received and so on.All can be done quickly and unlimited (Utari: 2011). In the development of social media today almost all of the majority alreadyhave accounts in social media, but in reality majority social media users are still notaware to utilize social media for positive things. It is certainly less useful in the use ofsocial media. Yet when viewed more deeply about the use of social media, manyentrepreneurs who really use social media as a suggestion of their business promotion,whether it is business in the field of culinary, fashion, IT to tourism.